INFLAMMATORY BOWEL DISEASE IN APPALACHIA: AN INVESTIGATION INTO DISPARATE OUTCOMES WITHIN THE STATE OF KENTUCKY. (22nd January 2022) - Perry, Courtney; Rhudy, Christian; Flomenhoft, Deborah; Talbert, Jeffrey; Barrett, Terrence
Abstract: INTRODUCTION: Inflammatory Bowel Disease (IBD) affects an estimated 3.1 million US adults, with an increasing prevalence in recent years 1 . Of these, 1.1 million live in the CDC classified "Southern" region, which includes the state of Kentucky. The eastern portion of the state is part of the Appalachian region, a low-resourced area with a dense, vulnerable population. The majority of Kentucky's Appalachian counties are classified as distressed (ranked bottom 10% in the US based on economic development), and suffer a higher prevalence of chronic disease 2 . To our knowledge, there is no published data quantifying the healthcare burden of IBD or evaluating disease outcomes in this vulnerable community. METHODS: We utilized the hospital inpatient discharge and outpatient services databases available through the healthcare cost and utilization project (HCUP) to assess outcomes among patients with a diagnosis of either Crohn's disease (CD) or Ulcerative Colitis (UC) in the state of Kentucky. Outcomes of interest were aggregated at the county level and included number of hospital admissions, number of total outpatient visits and visits to an emergency department, inpatient and outpatient surgeries. Data was reported as number of incident visits per 100, 000 population/year, collected between the years 2009-2019. RESULTS: We found that CD patients residing in Appalachian counties were more likely to be admitted to the hospital (42.72 vs. 29.69, p-value= 0.0001), require inpatient surgery (6.91 vs 5.35, p-value= 0.006), and be admitted for abdominal pain as a complication of their disease (3.82 vs 2.28, p-value = 0.0031) than non-Appalachians. Appalachian CD patients also had a higher number of ER visits (84.06 vs. 52.64, p-value = 0.0102), outpatient surgery visits (161.24 vs 112.35, p-value = 0.0024), and clinic visits for abdominal pain (39.8 vs 24.34, p-value=0.0002) than non-Appalachians. UC patients in Appalachian counties were more likely to require inpatient surgery (1.36 vs 0.74, p-value 0.0007) than non-Appalachians. There was no significant difference in rates of fistula, perforation, or malabsorption in either CD or UC based on Appalachian county data. CONCLUSION: These data support the notion of disparate outcomes in IBD based on Appalachian county residence in the state of Kentucky. This was most striking when evaluating Crohn's disease in Appalachians, as evidenced by hospital admissions, surgeries, and ER visits. Appalachian inpatients with UC had a significantly higher rate of surgical resection. These findings highlight a need for aggressive investigation into root causes of these disparate outcomes, with particular attention to identifying and subsequently alleviating barriers to IBD care. Whether these data infer treatment of Appalachian IBD patients should be managed more aggressively earlier in the disease course awaits further investigation.